A heat‐press‐treatment method for 3D printed thin‐walled composite structures with improved interfacial and compressive properties. Issue 11 (2nd September 2022) - Wang, Jin; Tan, Qianbing; Wang, Kui; Yao, Song; Peng, Yong; Rao, Yanni
Abstract: 3D printed thin‐walled composite structures suffered from the inherent low interlayer bonding, which limited the mechanical properties and influenced compressive behaviors. This work focused on effects of the postprocess on interfacial properties and compressive behaviors of thin‐walled composite structures made by fused deposition modeling. To improve the interfacial properties, a heat‐press‐treatment method was proposed. Compared to the nontreated thin‐walled structures, the energy absorption (EA) of the heat‐press‐treated structures increased from 61 to 90 J. It was found that both heat and pressure were indispensable conditions. The heat‐press‐treated thin‐walled structures presented a stable progressive collapse mode, while the heat‐treated structures without pressure collapsed in an unstable buckling manner due to the brittle fractures. The heat‐press‐treated structures presented higher crushing force efficiency (CFE) and EA than the heat‐treated structures. The difference was more significant with the increase of the treatment temperature from 50 to 200°C. Finally, the mechanisms of the improvement by the heat‐press‐treatment on interfacial bonding were analyzed. The findings of this research offered new insights on improving the EA for 3D printed thin‐walled composite structures. Abstract : 1. A heat‐press‐treatment method for 3D printed thin‐walled composite structures was proposed to improve interfacial and compressive properties. 2. The energy absorption performance of 3D printed thin‐walled composite structures was improved significantly by the heat‐press‐treatment. 3. The mechanisms of the improvement by the heat‐press‐treatment on interfacial bonding were analyzed.